007 Variability in point of care ultrasound (POCUS) practices in paediatric emergency departments in the UK & ireland; a PERUKI study. Issue 12 (21st November 2019) - Lyttle, Mark; Magnus, Dan; Kanani, Anand; Kehler, Lisa; Parri, Niccolo; Jones, Sarah
Abstract : Background: Point Of Care Ultrasound (POCUS) is a potentially useful addition to the technical armamentarium of PEM clinicians. Evidence is accumulating on diagnostic and procedural applications; however despite widespread use in other countries, usage patterns are not clear in our setting. Given the lack of a standardised PEM POCUS curriculum, best practice standards, and formal training courses, we aimed to determine variability in PEM POCUS practices across our PEM research network. Method and results: This online survey was distributed in March 2019, with content derived iteratively by the study team from existing literature and input from PERUKI members. One response was sought from each site, to describe department practices, hardware, and major enablers and obstacles. Results are presented using descriptive statistics. Conclusions: 59/63 (94%) sites responded, including a mix of site and department types (eg 40% tertiary hospital, 60% mixed adult/paediatric EDs, 30% major trauma centres). Almost all (90%) had access to POCUS, and 70% reported limited use by a small proportion of staff, with no named lead. Most (95%) did not have a teaching program or identified trainer. Approximately half (55%) routinely documented findings, most often in clinical notes, and most (65%) did not store images; most (68%) had no quality assurance measures. The greatest enablers of PEM POCUS were its need, funding for equipment, and clinician engagement; the greatest obstacles were availability of training courses and trainers, and time to learn and maintain skills due to service delivery needs. Whilst hardware is available in most EDs, PEM POCUS is not yet widespread, with training being the greatest obstacle. Future work exploring clinician opinions will inform whether the specialty wishes to embrace POCUS, and training course content. However, if adopted, it must be coupled with implementation of best practice standards in domains including quality assurance and governance.